CURRENT RATIO AND DEBT TO EQUITY RATIO TO THE PROFITABILITY OF FOOD AND BEVERAGE COMPANIES LISTED ON INDONESIA STOCK EXCHANGE (IDX) - Loppies, Lilian; Esomar, Maria J.F; Entatoning, Angel (jfpublisher, 2022)
This study aims to determine the effect of current ratio and debt to equity ratio on return on assets in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling method, the population was 24 food and beverage companies listed on the IDX during the study period, and there were 17 companies that met the requirements to be sampled. The data were analyzed using Multiple Linear Regression and data analysis used data processing software, called eviews 8. The results of this study indicate that the two independent variables tested on the return on assets of companies in the food and beverage sub-sector, the current ratio variable has a regression coefficient of 0.001740 and the level of significant at 0.6886. This means that H1 is rejected, and it can be said that the Current Ratio (CR) has no significant effect on Return on Assets (ROA). The variable Debt to Equity Ratio (DER) has a regression coefficient of -0.001027 and the significant value of 0.0010. This means that H2 is accepted and it concluded that the Debt to Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA).